Asymmetric hydrogenation of N-alkyl and N-aryl ketimines using chiral cationic Ru(diamine) complexes as catalysts: the counteranion and solvent effects, and substrate scope - Chen, Fei; Ding, Ziyuan; He, Yanmei; Qin, Jie; Wang, Tianli; Fan, Qing-Hua (Tetrahedron, 2012)
Asymmetric hydrogenation of N-alkyl and N-aryl ketimines catalyzed by chiral cationic η6-arene-(N-monosulfonylated diamine) Ru(II) complexes has been investigated. Strong counteranion and solvent effects on the enantioselectivity were observed. The ruthenium catalyst bearing non-coordinating BArF− anion was found to be particularly effective for the hydrogenation of acyclic and exocyclic N-alkyl ketimines in the presence of (Boc)2O in dichloromethane or even under solvent-free conditions, providing chiral amines with up to >99% ee and full conversions. Alternatively, the ruthenium catalyst bearing achiral phosphate anion together with corresponding phosphoric acid as the additive was also efficient for the hydrogenation of N-alkyl ketimines in the absence of (Boc)2O with excellent enantioselectivities and full conversions. For N-aryl ketimines lower enantiomeric excesses were observed by using the ruthenium catalyst bearing BArF− anion. This catalytic protocol thus provides a facile and practical access to optically active amines and has been successfully employed in the gram-scale synthesis of enantiomerically pure (+)-sertraline. [Display omitted]